A computational optimization study of a self-expandable transcatheter aortic valve. (December 2021) - Barati, Sara; Fatouraee, Nasser; Nabaei, Malikeh; Berti, Francesca; Petrini, Lorenza; Migliavacca, Francesco; Rodriguez Matas, Jose Felix
Abstract: Developing an efficient stent frame for transcatheter aortic valves (TAV) needs thorough investigation in different design and functional aspects. In recent years, most TAV studies have focused on their clinical performance, leaflet design, and durability. Although several optimization studies on peripheral stents exist, the TAV stents have different functional requirements and need to be explicitly studied. The aim of this study is to develop a cost-effective optimization framework to find the optimal TAV stent design made of Ni–Ti alloy. The proposed framework focuses on minimizing the maximum strain occurring in the stent during crimping, making use of a simplified model of the stent to reduce computational cost. The effect of the strut cross-section of the stent, i.e., width and thickness, and the number and geometry of the repeating units of the stent (both influencing the cell size) on the maximum strain is investigated. Three-dimensional simulations of the crimping process are used to verify the validity of the simplified representation of the stent, and the radial force has been calculated for further evaluation. The results suggest the key role of the number of cells (repeating units) and strut width on the maximum strain and, consequently, on the stent design. The difference in terms of the maximum strain between the simplified and the 3D model was less than 5%, confirming the validity of the adopted modeling strategy and the robustness of the framework to improve the TAV stent designs through a simple, cost-effective, and reliable procedure. Graphical abstract: Image 1 Highlights: This study investigates the structural optimization of transcatheter aortic valve stents. A cost-effective optimization framework for the self-expandable stent is presented. The framework focuses on minimizing the maximum strain during the stent crimping. 3D simulations of the crimping process are used to verify the optimization results. The number of cells and the strut width significantly influence the maximum stent strain during crimping.